No le pidas peras al olmo: La democracia en Centroamérica - Torres Rivas, Edelberto (Revista Española de Desarrollo y Cooperación, 2023)
The paper summarizes from a critical view the problems of consolidation of democracy in Central America. There is a brief reference to what it is called “authoritarian transition”. This refers in particular to three countries in the region in which there are developments concerning the stability of basic democratic institutions. It is talk of permanent transition processes or consummated. In Nicaragua, the current situation is the continuity of the post revolutionary sandinist in the government of Daniel Ortega facing critical situations. In Honduras, it is important to highlight the nature of the coup d’état of June 2009; and in El Salvador, the important political novelty, a guerrilla movement turned into a party that test democracy after an electoral victory.